Low-resistance ohmic contacts on boron-doped {113} oriented homoepitaxial diamond layers - Hazdra P.; Laposa A.; Šobáň Z.; Voves J.; Lambert N.; Davydova M.; Povolný V.; Taylor A.; Mortet V. (Elsevier Science, 2022)
Refractory metals (titanium, molybdenum, and zirconium) with a gold overlayer were used to form ohmic contacts on {113}-oriented boron doped diamond epitaxial layers (boron concentration ranging from 1019 to 1021 cm−3). Morphology and thickness of deposited layers were determined by AFM and X-SEM; resistivity, carrier concentration and mobility were determined by Hall measurement. Specific contact resistance RCsp of evaporated Ti/Au, Zr/Au, and Mo/Au contacts was measured using c-TLM structures after different annealing stages at temperatures up to 850 °C. Results show that on layers with {113} orientation it is possible to achieve ohmic contacts of comparable quality as for layers with {100} orientation. For all three metal systems, the lowest values for specific contact resistance reached 1 × 10−6 Ω.cm2. Ti/Au contacts show a stable ohmic behavior over the whole range of annealing temperatures, while Mo/Ti contacts had to be annealed above 500 °C to reduce the Schottky barrier and achieve good ohmic contact on lower B doped layers. Zr/Au contacts exhibit the lowest adhesion and required annealing to at least 700 °C to achieve ideal electrical and mechanical properties. Mo/Au and Zr/Au contacts on highly boron doped layers (~1021 cm−3) show excellent contacts when annealed at 700 °C, and therefore can be considered as improved candidates for ohmic contacts for diamond-based high-temperature power electronics than the conventional Ti/Au (Ti/Pt/Au) contact system. In summary, this study confirms the suitability of {113} oriented boron doped diamond epitaxial layers for the fabrication of diamond power electronic devices with excellent ohmic contacts.
Keywords: Diamond; Contacts; Boron-doping; Chemical vapor deposition; Contact resistance